Systematic review of carbapenem-resistant Enterobacteriaceae causing neonatal sepsis in China - Yijun Ding; Yajuan Wang; Yingfen Hsia; Mike Sharland; Paul T. Heath (BMC, 2019)
Abstract Background Carbapenems are β-lactam antibiotics which are used to treat severe infections caused by multidrug resistant Enterobacteriacea. The recent emergence and rapid spread of Enterobacteriaceae resistant to carbapenems is a global concern. We undertook a systematic review of the antibiotic susceptibility and genotypic characteristics of carbapenem-resistant Enterobacteriaceae in Chinese neonates. Methods Systematic literature reviews were conducted (PubMed/Medline, Embase, Wanfang medical online databases, China National Knowledge Infrastructure (CNKI) database) regarding sepsis caused by carbapenem-resistant Enterobacteriaceae in Chinese neonates aged 0-30 days. Results 17 studies were identified. Eleven patients in the six studies reported the source of infection. Ten patients (10/11, 90.9%) were hospital-acquired infections. Genotypic data were available for 21 isolates in 11 studies (20 K. pneumoniae, 1 E. coli). NDM-1 was the most frequently reported carbapenem-resistant genotype (81.0%, 17/21). Carbapenem-resistant Klebsiella pneumoniae and Escherichia coli were resistant to many antibiotic classes with the exception of colistin and fosfomycin. Sequence type 105 (ST105) was the most commonly reported K. pneumoniae ST type (30.8%; 4/13), which was from the same hospital in Western China. ST17 and ST20 were the second and third most common K. pneumoniae ST type, 23.1% (3/13) and 15.4% (2/13) respectively. The three strains of ST17 are all from the same hospital in central China. The two strains of ST20, although not from the same hospital, belong to the eastern part of China. Conclusions Klebsiella pneumoniae with the NDM-1 genotype was the leading cause of neonatal carbapenem resistant sepsis in China. Hospital acquired infection is the main source of carbapenem resistant sepsis. There is currently no licenced antibiotic regimen available to treat such an infection in China. Improved surveillance, controlling nosocomial infection and the rational use of antibiotics are the key factors to prevent and reduce its spread.